2018
DOI: 10.1103/physrevb.97.184434
|View full text |Cite
|
Sign up to set email alerts
|

Gapped ground state in the zigzag pseudospin-1/2 quantum antiferromagnetic chain compound PrTiNbO6

Abstract: We report a single-crystal study on the magnetism of the rare-earth compound PrTiNbO6 that experimentally realizes the zigzag pseudospin-1 2 quantum antiferromagnetic chain model. Random crystal electric field caused by the site mixing between non-magnetic Ti 4+ and Nb 5+ , results in the non-Kramers ground state quasi-doublet of Pr 3+ with the effective pseudospin-1 2 Ising moment. Despite the antiferromagnetic intersite coupling of about 4 K, no magnetic freezing is detected down to 0.1 K, whilst the system … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 72 publications
3
28
1
Order By: Relevance
“…[10] for Yb x Lu 1−x MgGaO 4 ] . The small Curie-Weiss temperature is obtained by the fit to χ measured in the temperature range where S m ∼ Rln2, and thus the CEF effect due to excitations to higher CEF levels is negligible, and we obtain θ w = -3(J zz 1 + J zz 2 )/2 (see below) [11,39]. Therefore, the magnetic ions should be almost homogeneously distributed in both diluted samples, otherwise significant Curie-Weiss temperatures should be expected.…”
Section: Single-ion Physicsmentioning
confidence: 67%
See 3 more Smart Citations
“…[10] for Yb x Lu 1−x MgGaO 4 ] . The small Curie-Weiss temperature is obtained by the fit to χ measured in the temperature range where S m ∼ Rln2, and thus the CEF effect due to excitations to higher CEF levels is negligible, and we obtain θ w = -3(J zz 1 + J zz 2 )/2 (see below) [11,39]. Therefore, the magnetic ions should be almost homogeneously distributed in both diluted samples, otherwise significant Curie-Weiss temperatures should be expected.…”
Section: Single-ion Physicsmentioning
confidence: 67%
“…A similar effective spin-1/2 Ising Hamilitonian with a continuous distribution of the microscopic parameters can be applied to other non-Kramers rare-earth magnets with correlated GS quasidoublets, such as the Pr 3+ effective spin-1/2 chain compound, PrTiNbO 6 , with the similar site-mixing disorder between nonmagnetic Ti 4+ and Nb 5+ ions [39]. Therefore, the correlated magnetism of the GS quasidoublets should be general as well in condensed matter physics, as the structural disorder is usually inevitable in a real material.…”
Section: Phase Diagram and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The very similar results were also reported in the kagome Ising antiferromagnet with even larger S m (0 K) ≈ 72.40% R ln2, and in the pyrochlore Ising ferromagnet with smaller S m (0 K) ≈ 29.25% R ln2, respectively. Further studies found the macroscopic GS degeneracy of a classical Ising system may be easily lifted by various kinds of perturbations, such as the second‐neighbor interaction and bond randomness, which are usually inevitable in a real material.…”
Section: Introductionmentioning
confidence: 99%